2016
DOI: 10.1002/clen.201400377
|View full text |Cite
|
Sign up to set email alerts
|

Annual Carbon Gas Emissions from a Boreal Peatland in Continuous Permafrost Zone, Northeast China

Abstract: Peatland is a significant ecosystem that has accumulated one-third of the soil carbon in boreal regions. However, the net carbon balance, particularly with current carbon emissions, remains unclear. In this study, the annual ecosystem respiration and CH 4 fluxes from a peatland located in Northeast China are reported. Ecosystem respiration fluxes from the shrub-moss-and Eriophorum-dominated communities in the peatland varied from 12 to 272 mg C m À2 h À1 during the snow-free season, and the Eriophorumdominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…The CH 4 emissions ranged from −0.248 to 11.459 mg m −2 hr −1 and were higher than those reported for Alaska (0.256–7.8 mg m −2 hr −1 ; Myers‐Smith et al., 2007; Wickland et al., 2006), subarctic (−0.02–6.36 mg m −2 hr −1 ; Jammet et al., 2017; Voigt et al., 2017), northeast China (−1.8–4.8 mg m −2 hr −1 ; Liu et al., 2015; Miao et al., 2016; Sun et al., 2018), Tibetan Plateau (−22.6–4.7 mg m −2 hr −1 ; Chen et al., 2017; Yang, Peng, Olefeld, et al., 2018; Yun et al., 2018), Siberia (−0.013–1.024 mg m −2 hr −1 ; Takakai et al., 2008a, 2008b), and Canada (∼0 mg m −2 hr −1 ; Turetsky et al., 2007). Generally, the CH 4 emissions from the Daxing'an Mountains were higher than those of other permafrost regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CH 4 emissions ranged from −0.248 to 11.459 mg m −2 hr −1 and were higher than those reported for Alaska (0.256–7.8 mg m −2 hr −1 ; Myers‐Smith et al., 2007; Wickland et al., 2006), subarctic (−0.02–6.36 mg m −2 hr −1 ; Jammet et al., 2017; Voigt et al., 2017), northeast China (−1.8–4.8 mg m −2 hr −1 ; Liu et al., 2015; Miao et al., 2016; Sun et al., 2018), Tibetan Plateau (−22.6–4.7 mg m −2 hr −1 ; Chen et al., 2017; Yang, Peng, Olefeld, et al., 2018; Yun et al., 2018), Siberia (−0.013–1.024 mg m −2 hr −1 ; Takakai et al., 2008a, 2008b), and Canada (∼0 mg m −2 hr −1 ; Turetsky et al., 2007). Generally, the CH 4 emissions from the Daxing'an Mountains were higher than those of other permafrost regions.…”
Section: Discussionmentioning
confidence: 99%
“…The ranges of CO 2 emissions from the Daxing'an Mountains were within the range of previous publications. The thermokarst lakes are considered “hot spots” for CO 2 emissions; the average CO 2 emission is 1,876 mg m −2 hr −1 , higher than the peak CO 2 emission from the Daxing'an Mountains (Liu et al., 2015; Miao et al., 2016; Wickland et al., 2006). Permafrost thawing would cause the decomposition of fixed carbon, promoting the release of CO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al [41] predicted that permafrost areas would decline to an estimated 35% of that amounts in the 1970s and 1980s if air temperature increases 1.0 to 1.5 • C during the next 40-50 years. Some studies have reported GHG emissions in this region [42][43][44][45][46][47]. Among these studies, Miao et al [42,43] and Cui et al [44] discussed the relationship between GHG emissions and active layer depth in one peatland site.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported GHG emissions in this region [42][43][44][45][46][47]. Among these studies, Miao et al [42,43] and Cui et al [44] discussed the relationship between GHG emissions and active layer depth in one peatland site. Liu et al [45] studied but did not find a relationship between the active layer depth and GHG emissions.…”
Section: Introductionmentioning
confidence: 99%